Analysis of Administrative Service Systems at the Land Office in Takalar District - Syahrul Syahrul (Universitas Negeri Makassar, 2019)
The administrative service system at the Takalar District Land Office has been good and in accordance with Service Standards according to Law Number 25 of 2009 concerning Public Services and State Minister for the Empowerment of State Apparatus (MENPAN) Decree Number 63 of 2003 concerning general guidelines The approach used in this study is a Qualitative Approach. Data analysis used the opinion of Miles, Huberman, and Saldana (2014) regarding the interactive model of policy research that looked at data reduction, data condensation, data presentation, and conclusion drawing. This process continues throughout the research, even before the data is actually collected The administrative service system has been carried out in accordance with the implementation of public services according to the procedures established by law as well as: 1) Procedure in managing land administration according to the service flow and clarity of information is quite clear; 2) The completion time of all land administration arrangements can be done on time; 3) Land administration service costs based on the level of land management; 4) Service products; 5. Facilities and infrastructure can support services to the community; 6. The service of the clerk is quite good. Analysis of Administrative Service Systems at the Land Office in Takalar District